Risk factors of incomplete balloon-assisted enteroscopy with an analysis of 943 patients: a retrospective study - Liu, Jun; Wan, Meng; Wang, Peng; Guo, Jing; Yu, Yan-Bo; Zuo, Xiu-Li (Frontiers in Medicine, 2025)
BackgroundBalloon-assisted enteroscopy (BAE) plays an important role in the diagnosis and therapy of small bowel diseases. Complete enteroscopy is considered an objective quality indicator of enteroscopy. However, there are limited studies on the factors associated with complete BAE. This study aimed to determine the factors affecting complete BAE.MethodsAll adult patients with indications for BAE were investigated at a tertiary medical center from January 2019 to December 2022. Their medical records and BAE procedure-associated data were reviewed and analyzed. Risk factors of incomplete enteroscopy were investigated using univariate analysis and multivariable logistic regression analysis.ResultsA total of 943 patients meeting the eligibility criteria were analyzed. Among these, 558 patients achieved complete enteroscopy. In multivariable logistic regression analysis, single-balloon enteroscopy (SBE) [odds ratio (OR) = 2.35, 95% confidence interval (CI): 1.79–3.09, p < 0.001], male sex (OR = 1.62, 95% CI: 1.22–2.15, p = 0.001), intestinal surgery (OR = 2.26, 95% CI: 1.79–3.09, p = 0.003), and body mass index (BMI) ≥ 28 kg/m2 (OR = 1.20, 95% CI: 1.07–1.34, p = 0.002) were independent predictors of incomplete enteroscopy.ConclusionThis retrospective study identified SBE, male sex, intestinal surgery, and BMI ≥ 28 kg/m2 as independent risk factors for incomplete enteroscopy.